EVALUASI PEMBINAAN PRESTASI DI KLUB BOLAVOLI INDOMARET SIDOARJO - Utomo, Budi (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to evaluate the performance development program at the Indomaret Volleyball Club Sidoarjo in order to determine the factors causing the performance decline at the first division volleyball league in the past year national championship. This research is qualitative techniques using a SWOT analysis model, including development for athletes, coaches, training programs, funding and infrastructure. The subjects in this research were officials and athletes consisting of 2 coaches, 1 assistant manager and 13 athletes. Data collection in this research using questionnaires, interviews and documentation. The conclusion of this research, the factors causing decreased in performance of the Indomaret volleyball club in the first division volleyball league national championship in the past year were: (1) In 2019 there were 5 core players of the Indomaret club who undergoing training camps with the Indonesian National Team at the volleyball hermitage in Bogor for the SEA Games in the Philippines, and only getting permission to play when the first division volleyball league championship was held, so the Indomaret club could not train as a team which resulted in less compact of the players when playing, and also communication while on the court. (2) Does not have a written training program including a schedule for participating in competition before the main match. (3) In addition, the Indomaret club does not yet have test and measurement procedures, so there is no the ability data of each athlete who is sent in the main competition, both from a technical and physical.